"Why Doesn't Anyone Help Us?": Therapeutic Implications of Black Girls' Perceptions of Health. Issue 3 (2nd October 2019) - Jernigan, Maryam M.
Abstract: The prevalence of overweight and obesity among Black adolescent girls has continued to increase significantly since the 1980s, which indicates that Black girls are disproportionately affected by the obesity health crisis. In addition to risks for negative physical health outcomes, Black girls face the poor psychosocial and emotional consequences of increased weight. Yet, they are less likely to have access to or seek effective treatment. Mixed-methods methodologies were used to examine focus-group responses ( N  = 15) of Black girls' perceptions of their health and the factors that they believe influence wellness. Participants cited conflicting information from medical providers and lack of health knowledge as barriers to a healthy lifestyle. They also indicated that their families and communities either promoted or deterred their health outcomes. The unique social experiences of Black girls that facilitate the types of health-compromising behaviors that result in increased weight are highlighted. Recommendations for mental health providers, families, and schools are offered.